Estimation of regional mass balance changes of the Greenland ice sheet using GRACE data and the Input-output method - Xu, Z. (author) (2019)
In the 21st century, polar land ice melting became one of the driving factors of global sea level rise, which is discussed widely by the media and the public. Although the fact of the shrinking ice caps and accompanying changes in the sea level is established, the actual amount of polar ice melting still needs to be quantified in separate regions. Sitting on top of bedrock, the Greenland ice sheet (GrIS) is the second largest ice sheet on Earth. With traditional glaciological methods the change of the Greenland ice sheet is difficult to measure directly, however with the GRACE (Gravity Recovery and Climate Experiment) satellite system the mass changes can be measured directly. There are several sub-drainage areas within the Greenland Ice Sheet. Some of the subsystems may contribute differently to the overall mass changes of GrIS. For instance, while the mass loss in the GrIS ablation zone is enhanced during the last decades, the central high altitude areas experienced increased mass accumulation (Krabill et al., 2000, Thomas et al., 2001, Colgan et al., 2015, Xu et al., 2016). It is important to quantify the regional mass changes because it gives us insight what is going on beyond the realization that the GrIS is shrinking. Astrodynamics & Space Missions